Pelatihan Pembuatan Eco-Friendly Light-Brick dari Sekam Padi sebagai Bata Ringan Tahan Gempa di Dusun Mriyan Utara Kabupaten Bantul - Setyani, Atik; Prabowo, Imam; Arif, Nina Fapari; Ichsanudin, Muhammad; Pranoto, Aditya Wahyu; Tantrianita, Rikma; Pradipa, Raditya Khayru (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service activity aims to enhance the skills of the Karang Taruna in Dusun Mriyan Utara, Bantul Regency, in making eco-friendly light bricks from rice husk as earthquake-resistant lightweight bricks. The method used in this community service involves participatory training, where youth groups actively make light bricks from natural waste. The evaluation instruments for this activity include direct observation and post-tests, which are analyzed descriptively to measure the participants' improvement in skills and knowledge. The results of this community service indicate that the people of Dusun Mriyan Utara are very enthusiastic and have successfully improved their skills in making light bricks, which can be developed as a flagship product of the village and a preventive measure in earthquake disaster mitigation.